Saved or not? speaker meaning attributed to salvation and Ukusindiswa in a church context - Kerr, Nicholas Brabazon (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (General Linguistics))—University of Stellenbosch, 2009.